Renal and segmental pancreatic grafting with draining of exocrine secretion and initial continuous intravenous cyclosporin A in a patient with insulin-dependent diabetes and renal failure - Calne, R Y (1982)
A patient with renal failure and insulin-dependent diabetes received renal and segmental pancreatic allografts from the same donor, with exocrine drainage of the pancreas being directed into the bowel. An attempt was made to maintain the serum concentrations of cyclosporin A between 300 and 1000 μg/l to avoid serious nephrotoxicity and rejection. Considerable difficulty was experienced in controlling the serum concentrations even with continuous intravenous infusion. When the concentrations were maintained between 300 and 1000 μg/l function in both allografts was satisfactory. At seven months the patient required no insulin and had good renal function. He was not receiving corticosteroids.